2019
DOI: 10.1177/1947603519828433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antibiotics on α-Toxin Levels during Staphylococcus aureus Culture: Implications for the Protection of Chondrocytes in a Model of Septic Arthritis

Abstract: toxin levels during Staphylococcus aureus culture: implications for the protection of chondrocytes in a model of septic arthritis.', Cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…27,28 As reported by Smith et al, 27,28 we utilized chondrocyte viability 24 hours following S aureus inoculation as our experimental endpoint to investigate the efficacy of PRP, AmpS, and PRP+AmpS treatments. The S aureus-derived toxin α-hemolysin is the key toxin responsible for rapid chondrocyte death with this model, 26,28 and both S aureus strains used in this study, ATCC 29213 and 43300, secrete α-hemolysin toxin. [36][37][38] The S aureus inoculum size used in this Figure 1-Box-and-whisker plots of metabolic activity (optical density) of bovine cartilage explants incubated with synovial fluid (SF) alone or incubated with S aureus-inoculated SF (SA) alone or with platelet-rich plasma (PRP; 25% culture medium volume; SA+PRP), ampicillin-sulbactam (AmpS; 2 mg/mL; SA+AmpS), or both PRP (25% culture medium volume) and AmpS (2 mg/ mL; SA+PRP+AmpS) for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 As reported by Smith et al, 27,28 we utilized chondrocyte viability 24 hours following S aureus inoculation as our experimental endpoint to investigate the efficacy of PRP, AmpS, and PRP+AmpS treatments. The S aureus-derived toxin α-hemolysin is the key toxin responsible for rapid chondrocyte death with this model, 26,28 and both S aureus strains used in this study, ATCC 29213 and 43300, secrete α-hemolysin toxin. [36][37][38] The S aureus inoculum size used in this Figure 1-Box-and-whisker plots of metabolic activity (optical density) of bovine cartilage explants incubated with synovial fluid (SF) alone or incubated with S aureus-inoculated SF (SA) alone or with platelet-rich plasma (PRP; 25% culture medium volume; SA+PRP), ampicillin-sulbactam (AmpS; 2 mg/mL; SA+AmpS), or both PRP (25% culture medium volume) and AmpS (2 mg/ mL; SA+PRP+AmpS) for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we reported the chondrocyte death-mitigating effects of PRP and AmpS, it must be noted that S aureus inoculation and PRP+AmpS treatments were initiated simultaneously in this study, and this does not mimic clinical scenarios. Inoculating explants with S aureus prior (ie, 12 to 14 hours) to adding treatments and subsequently quantifying chondroprotective indices relative to untreated controls as described by Miller et al 26 would have been more reflective of clinical septic arthritis. Platelet concentrations in PRP treatments between experiments from individual cattle were not standardized to control for intersubject variability of quantified outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] Binding of Hla to ADAM10 receptors on chondrocytes leads to cell membrane pore formation, and influx of Na + and water, causing cell lysis. 31 An example of Hlatargeted therapy lies in the choice of antibiotics as shown by Miller et al, 32 whereby a bacteriostatic antibiotic linezolid showed rapid curtailing of Hla-induced haemolysis in the rabbit erythrocyte assay. The action of linezolid was faster compared to the bacteriolytic antibiotic penicillin.…”
Section: Discussionmentioning
confidence: 99%
“…A hemolysis assay was performed as previously described (Miller et al, 2021). Approximately 10 ml of whole blood was collected from the central auricular artery of a New Zealand male rabbit, which was purchased from the Laboratory Animal Center of the Third Military Medical University, and added to 1 ml heparin sodium solution, followed by three times of wash with PBS with centrifugation at 1,000 × g for 5 min at 4 • C. A concentration of 2% (v/v) rabbit red blood cells (RBCs) was prepared with PBS.…”
Section: Hemolysis Assaymentioning
confidence: 99%